What Is Judicial Ideology, and How Should We Measure It? - Fischman, Joshua B. (Washington University journal of law and policy, 2009)
Part I of this Article explores the theoretical problem that scholars use the term “judicial ideology” in the absence of any widespread agreement or clear understanding as to what the term means in the first place. It is difficult for scholars to devise appropriate and broadly acceptable measures of judicial ideology when they and their readers have different concepts—or perhaps no coherent concept at all—of “judicial ideology” in mind. As a result, bona fide intellectual disagreement over the nature of judicial behavior is too easily compounded by outright misunderstanding. Part II discusses three of the most significant and common practical obstacles to the measurement of judicial ideology. First, ideology is not a tangible phenomenon that can be directly observed. Second, judicial behavior is often open to multiple interpretations. Third, judicial ideology may be a multidimensional phenomenon, such that a judge who is liberal in one context may be moderate or conservative in another, or the labels “liberal,” “moderate,” and “conservative” may not seem applicable at all. Parts III and IV of this Article aim to address an important practical need of judicial behavior scholars. There are several ways in which one can measure judicial ideology, but little has been written about how researchers should go about choosing among these methods. Competing considerations of accuracy, convenience, and ease of interpretation make it difficult to know what measurementapproach is most appropriate to the task at hand. In Part III, the relative merits of three popular approaches are identified and discussed: the use of proxy measures, the assessment of judicial ideology based on the actual behavior of the judges in a particular context, and the transplantation of ideology measures developed in one context into other contexts involving partly or wholly different data. Finally, in Part IV, the real-world performance of different measurement approaches are compared, using data drawn from the federal courts of appeals and the Supreme Court